Pengaruh Aditif Gliserol Terhadap Stabilitas Thermal Biopolimer Karagenan dari Eucheuma cottonii pada Kondisi Salinitas 5000 ppm dan Suhu 60 °C - Ulfah, Rosi; Manik, Nijusiho; Risna, Risna; Hutabarat, Romauli Tiurma (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the impact of glycerol additives on the thermal stability of carrageenan biopolymers from Eucheuma cottonii at a salinity of 5000 ppm and a temperature of 60 °C, which serves as a simulation for Enhanced Oil Recovery (EOR) reservoirs. Carrageenan solutions were designed with varying glycerol concentrations, then tested for viscosity at room temperature and after heating using a viscometer. The results showed that the addition of glycerol had a significant effect on viscosity stability. The idea glycerol concentration was able to reduce the decrease in viscosity caused by heating, while too much glycerol actually reduced the effectiveness of the polymer due to its plasticizer effect. This study recommends the use of glycerol at an optimal concentration to improve the thermal stability of carrageenan as an environmentally friendly biopolymer alternative for EOR applications with a salinity level of 5000 ppm.